(untitled) (Docentes 2.0 Journal, 2026)
Secondary education faces challenges, including student demotivation, a disconnect between the curriculum and the realities of youth, and the predominantly instrumental use of educational technologies. In this context, it is necessary to promote pedagogical strategies that reframe the meaning of learning and strengthen youth empowerment from critical and situated educational perspectives. The objective of this article was to reflect upon the virtual store as a situated pedagogical experience for youth empowerment in secondary education. The research was conducted under the sociocritical paradigm, employing an interpretive-critical method with a qualitative approach and a design based on the reflective systematization of a pedagogical experience, specifically a descriptive-interpretive, cross-sectional study. The participants included 30 tenth- and eleventh-grade students and three teachers from three public educational institutions in Bucaramanga. Data collection was conducted through systematic pedagogical observation, semi-structured interviews, focus groups, and field journal entries, complemented by participatory validation. The analysis was conducted through thematic categorization and the triangulation of the various data sources. The results demonstrate that the virtual store, understood as a form of pedagogical mediation that extends beyond mere instrumental use, fostered active participation, decision-making, and meaning-making among students by articulating academic knowledge with meaningful social practices. It is concluded that the virtual store, conceived as a situated pedagogical experience, contributes to reframing learning and strengthening youth empowerment, thereby opening up possibilities for a more relevant, inclusive, and transformative secondary education.